MEMBANGUN KEPRIBADIAN DAN KARAKTER MELALUI AKTIFITAS OLAHRAGA - Kardiyanto, Deddy (Jurnal Phederal Penjas, 2015)
Sportmanship is a morality in sport. Good sport activity is a reflection of well sport application. Related to human trait as learning creature, sport activity can be used as a way to develop character or personality. Transfer of morality values can be done through sport activity directly as player, official, supporter or spectator in sport arena, or undirectly through live or replay television broadcast. For the need of personality and character development, can be choosen sport program that reflecting good sportmanship applying.Key Words: Sportmanship, Character, and Sport.